Re-examination of the APETALA2/Ethylene-Responsive Factor Gene Family in Barley (Hordeum vulgare L.) Indicates a Role in the Regulation of Starch Synthesis - Ding, Jinjin; Karim, Hassan; Li, Yulong; Harwood, Wendy; Guzmán, Carlos; Lin, Na; Xu, Qiang; Zhang, Yazhou; Tang, Huaping; Jiang, Yunfeng; Qi, Pengfei; Deng, Mei; et al. (Frontiers in Plant Science, 2021)
The APETALA2/Ethylene-Responsive factor (AP2/ERF) gene family is a large plant-specific transcription factor family, which plays important roles in regulating plant growth and development. A role in starch synthesis is among the multiple functions of this family of transcription factors. Barley (Hordeum vulgare L.) is one of the most important cereals for starch production. However, there are limited data on the contribution of AP2 transcription factors in barley. In this study, we used the recently published barley genome database (Morex) to identify 185 genes of the HvAP2/ERF family. Compared with previous work, we identified 64 new genes in the HvHvAP2/ERF gene family and corrected some previously misannotated and duplicated genes. After phylogenetic analysis, HvAP2/ERF genes were classified into four subfamilies and 18 subgroups. Expression profiling showed different patterns of spatial and temporal expression for HvAP2/ERF genes. Most of the 12 HvAP2/ERF genes analyzed using quantitative reverse transcription–polymerase chain reaction had similar expression patterns when compared with those of starch synthase genes in barley, except for HvAP2-18 and HvERF-73. HvAP2-18 is homologous to OsRSR1, which negatively regulates the synthesis of rice starch. Luciferase reporter gene, and yeast one-hybrid assays showed that HvAP2-18 bound the promoter of AGP-S and SBE1 in vitro. Thus, HvAP2-18 might be an interesting candidate gene to further explore the mechanisms involved in the regulation of starch synthesis in barley.